Exploring Cation Diffusion to Redox Species Encapsulated in Carbon Nanotubes - Mortiboy, Beth (2022)
The transport of ions through carbon nanotube systems has been studied extensively. However, there is limited evidence of ion transport via nanotube sidewalls. Using a novel host-guest redox active hybrid material, insight into the mechanisms of ion transport within carbon nanotubes can be assessed using very simple electrochemical techniques. Here we utilise a system whereby polyoxometalates (POMs) are encapsulated within single-walled carbon nanotubes (SWNTs). The POM acts as a redox probe and can measure the effectiveness of ion transport throughout the material. The diffusion of large cationic species (Li+, Na+, K+, NH4+) throughout the system is limited and the mechanism of their transport can be confirmed using a simple blocking technique, whereby the open ends of the SWNT become inaccessible to such ions. The kinetic isotope effect of proton and deuteron transport throughout the systems was found to be 1.32 and 1.21 for two aqueous acidic electrolyte systems. This value is significantly lower than what is reported for other systems focusing on the permeation of these ions through similar one-atom thick membranes. It can be concluded that for practical application within electrochemical systems, the rate of transport of both H+ and D+ is sufficiently fast and that the permeation of these ions through the nanotube system is not rate limiting.